Communicating Climate Change in Kenya: Status, Challenges and Prospects - Momanyi, Elizabeth; Nyatuka, Benard O. (Advances in Social Sciences Research Journal, 2015)
Climate change remains a gigantic developmental issue the world over thus calling for sustainable intervention measures. Research shows that despite the potential dangers posed by climate change, public concern is low, a situation that tends to be linked to unfamiliarity with the nature of the climate uncertainties. One of the possible ways to address this scenario, it has been argued, is to apply research from communication and related fields to tailor messages to the existing perceptions, values and attitudes of different audiences in a bid to make the debate understandable, relevant and personally important. And, this is where journalists are called upon to not only present the complicated story, but make it comprehensible and appealing to a lay readership as well. But what challenges are they likely to face in communicating issues on climate change? To attain the goals envisioned in the Kenya Vision 2030 in particular, and socio-economic development in general, understanding climate change, its attendant consequences and the most appropriate means to tackle them is paramount. Specifically, this paper discusses the challenges facing journalists in covering climate change issues in Kenya. Prospects with respect to communicating climate change issues in the country are also explored. In an attempt to better understand this paper, a relevant theory is elucidated while the background information is presented including an overview of climate change, the status of the mitigation measures being employed as well as the role of the media in communicating this grave phenomenon.